Radiotherapy in oesophageal cancer - Leborgne (h), Félix (Cirugía del Uruguay, 1975)
Nineleen ( 2.1 %) oí 903 patients scen with cnr einoma o( ocsophagus (1950-66) are alivc with no evicI.ence oE discasc 5 years aft.er l'adiation therapy. Dut·ing lhe period 1950-71, 23 patie-nts were 5 years ,.;urvivors, but 61 ~ presented with local recurrencc 01' mdi'lstatic diseasc aíter 5 years. The leading cause of death :s sUll cancel' in long 1erm survivors. Radiotherapy improves dysphagia in 80 <;{ of patients submitted to radical treatment, with no apparen\ complications. This modality is recommended for al! sites of oesophagea! squamous cell carcinoma. with emphasis on íemale patients who !.!&rTy a better prognosis.